Upper limb disability in Norwegian workers with hand-arm vibration syndrome - Buhaug, Kristin (BioMed Central, 2014)
BACKGROUND: Hand-arm vibration syndrome (HAVS) is a well-known disease among workers using hand-held vibrating tools. These patients experience major symptoms from their upper limbs. However, there are few studies on disability in this patient group. In this study we wanted to describe the disability of HAVS patients. METHODS: All HAVS patients diagnosed at Haukeland University Hospital in Bergen, Norway in a five-year period were invited. The disabilities of the arm, shoulder and hand (DASH) questionnaire was sent by mail. Clinical data were extracted from their hospital journals. Descriptive statistics and regression analyses were performed. RESULTS: Thirty-eight patients were recruited. Mean DASH score was 41.2, while the mean of a normal population is 10. Ability to perform tasks related to work and everyday life was affected in these patients. We found a significant association between the DASH score, hand grip strength and tendinitis, also after adjustment for age and smoking in pack-years. CONCLUSION: HAVS patients demonstrate a high level of upper limb disability as assessed by the DASH score. Ability to perform tasks related to work and everyday life was affected. We found a significant association between the DASH score, hand grip strength and tendinitis. This should be focused upon in future research.